2019
DOI: 10.21203/rs.2.9645/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cutaneous Leishmaniasis A Neglected Tropical Disease: Community Knowledge, Attitude And Practices In An Endemic Area, Northwest Ethiopia

Abstract: BackgroundCutaneous leishmaniasis is one of the neglected tropical diseases in the Ethiopian highlands and studies on assessment of knowledge, attitude and practice of the community in endemic areas are scanty. The study aimed to assess the knowledge, attitude towards cutaneous leishmaniasis and treatment seeking practices in people living in the endemic highlands areas in the Northwest, Ethiopia and provide evidence-based information to guide development of appropriate interventions to reduce the impact of cu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The increasing number of suspected cases might be related to an increase in health-seeking behavior of the people. A few studies in this study area indicated that people believe that the disease is caused by bats, and others related the disease to lack of hygiene and punishment from God [28]. Previously, due to the limited availability of antileishmanial drugs, there was a trend to prioritize VL.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The increasing number of suspected cases might be related to an increase in health-seeking behavior of the people. A few studies in this study area indicated that people believe that the disease is caused by bats, and others related the disease to lack of hygiene and punishment from God [28]. Previously, due to the limited availability of antileishmanial drugs, there was a trend to prioritize VL.…”
Section: Discussionmentioning
confidence: 91%
“…This may indicate that the existing prevention and control measures are not effective enough in reducing the cases of the disease. In Ethiopia, CL diagnosis and treatment services are given only in a few health care facilities, and most are available in areas far from places where the actual patients are residing [28]. This could have complicated the prevention and control of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Emphasizing the need for controlling this disease Ministry of health, Sri Lanka declared it as a noti able disease in 2008 (15). As expected, doctors were more knowledgable about the clinical features, causative organism, disease transmission and the vector of Leishmaniasis compared to the studies done in general public (16,17). But only 17% of respondents were aware that cutaneous leishmaniasis can be cured even without treatment.…”
Section: Discussionmentioning
confidence: 87%
“…Emphasizing the need for controlling this disease Ministry of health, Sri Lanka declared it as a notifiable disease in 2008 [11]. As expected, doctors were more knowledgable about the clinical features, causative organism, disease transmission and the vector of Leishmaniasis compared to the studies done in the general public [15,16]. But only 17% of respondents were aware that cutaneous leishmaniasis can be cured even without treatment.…”
Section: Discussionmentioning
confidence: 88%